WITH RESPECT TO CHILDREN - NIKALJE, VARADA M. (THE PRIMARY TEACHER, 2014)
The National Curriculum Framework (NCF) 2005 developed by NCERT has for one of its guiding principles the connecting of knowledge to life outside the school. Consequently, the post2005 textbooks brought out by NCERT followed this principle, with the happy result that pedagogically speaking, the textbooks were more user-friendly and encouraged critical thinking. One of the textbooks in English published by NCERT has a short piece on the tsunami of 2004. As is well-known, the South Asian tsunami, also called Boxing Day tsunami, occurred on Sunday, 26 December 2004. It had a devastating effect along the coasts of most landmasses bordering the Indian Ocean, killing over 2,30,000 people in 14 countries. It was one of the deadliest natural disasters in recorded history. The excerpt in the Class VIII textbook (English) narrates how the Smith family from South-East England were celebrating Christmas at a beach resort in Phuket, Thailand. Tilly Smith, a ten-year old school girl, along with her younger sister and parents, was on the beach on 6 December 2004. Tilly saw the sea slowly rise, and start to foam, bubble and form whirlpools. She sensed that something was wrong. The excerpt reads: ‘Tilly started to scream at her family to get off the beach. “She talked about an earthquake under the sea. She got more and more hysterical,” said her mother Penny. “I didn’t know what a tsunami was.” The family went back to the hotel. Other tourists also left the beach with them. The family took refuge in the third floor of the hotel. The building withstood the surge of three tsunami waves.’ The excerpt goes on to say that thanks to Tilly and her geography lesson, they were saved.